Nuclear Imaging in Pediatric Cardiology: Principles and Applications - Venet, Maelys; Friedberg, Mark K.; Mertens, Luc; Baranger, Jerome; Jalal, Zakaria; Tlili, Ghoufrane; Villemain, Olivier (Frontiers in Pediatrics, 2022)
Nuclear imaging plays a unique role within diagnostic imaging since it focuses on cellular and molecular processes. Using different radiotracers and detection techniques such as the single photon emission scintigraphy or the positron emission tomography, specific parameters can be assessed: myocardial perfusion and viability, pulmonary perfusion, ventricular function, flow and shunt quantification, and detection of inflammatory processes. In pediatric and congenital cardiology, nuclear imaging can add complementary information compared to other imaging modalities such as echocardiography or magnetic resonance imaging. In this state-of-the-art paper, we appraise the different techniques in pediatric nuclear imaging, evaluate their advantages and disadvantages, and discuss the current clinical applications.